Interações rocha-fluido e geomecânica de fraturas: utilização de processos WAG em condições de Pré-sal - Barbosa, Thiago Henrique da Silva (2021)
In 2020, more than two-thirds of the consolidated Brazilian production of hydrocarbons was supplied by the Pre-salt province, with an increasing trend already in the first months of 2021. In this sense, in addition to the complexities proposed by the characteristics intrinsic to carbonate reservoirs, within the scope of characterization and monitoring of production, the optimization of recovery methods widely used in these accumulations receives an important appeal, because of the significant dependence on the economic sector. Thus, this work proposes to investigate the dynamic behavior of reservoirs in Pre-Salt conditions submitted to water alternating gas injection processes (WAG) by investigating factors of rock-fluid interactions and the presence of anisotropies brought about by fractures. For this purpose, compositional numerical simulation methods were used to evaluate scenarios involving saturation history problems and further investigate the geomechanical impacts on recovery caused by fracture reactivation. The results of the incorporation of hysteresis demonstrate a significant reduction in the mobility of the injected water and gas plumes and a consequent decrease in the production of these fluids. Furthermore, the addition of fractures and the reactivations proposed by the Barton and Bandis model showed a broad influence on production, especially in the most heterogeneous scenarios.